Thermally activated delayed fluorescence materials for nondoped organic light‐emitting diodes with nearly 100% exciton harvest. Issue 1 (27th May 2022) - Fan, Xiao‐Chun; Wang, Kai; Shi, Yi‐Zhong; Sun, Dian‐Ming; Chen, Jia‐Xiong; Huang, Feng; Wang, Hui; Yu, Jia; Lee, Chun‐Sing; Zhang, Xiao‐Hong
Abstract: High‐performance nondoped organic light‐emitting diodes (OLEDs) are promising technologies for future commercial applications. Herein, we synthesized two new thermally activated delayed fluorescence (TADF) emitters that enable us, for the first time, to combine three effective approaches for enhancing the efficiency of nondoped OLEDs. First, the two emitters are designed to have high steric hindrances such that their emitting cores will be suitably isolated from those of their neighbors to minimize concentration quenching. On the other hand, each of the two emitters has two stable conformations in solid films. In their neat films, molecules with the minority conformation behave effectively as dopants in the matrix composing of the majority conformation. One hundred percent exciton harvesting is thus theoretically feasible in this unique architecture of "self‐doped" neat films. Furthermore, both emitters have relatively high aspect ratios in terms of their molecular shapes. This leads to films with preferred molecular orientations enabling high populations of horizontal dipoles beneficial for optical out‐coupling. With these three factors, OLEDs with nondoped emitting layers of the respective emitters both achieve nearly 100% exciton utilization and deliver over 30% external quantum efficiencies and ultralow efficiency roll‐off at high brightness, which have not been observed in reported nondoped OLEDs. Abstract : Two thermally activated delayed fluorescence molecules are designed by strategically integrating three effective strategies: (1) bulky peripheral side groups; (2) "self‐doping" configuration induced by dual conformation; (3) highly ordered horizontal orientations. Nondoped organic light‐emitting diodes (OLEDs), using the two new emitters deliver 100% exciton utilization, record‐high maximum external quantum efficiencies of over 30%, and ultralow efficiency roll‐off for the first time.